Reducing placebo exposure in trials: Considerations from the Research Roundtable in Epilepsy. (3rd October 2017) - Fureman, Brandy E.; Friedman, Daniel; Baulac, Michel; Glauser, Tracy; Moreno, Jonathan; Dixon-Salazar, Tracy; Bagiella, Emilia; Connor, Jason; Ferry, Jim; Farrell, Kathleen; Fountain, Nathan B.; French, Jacqueline A.
Abstract : The randomized controlled trial is the unequivocal gold standard for demonstrating clinical efficacy and safety of investigational therapies. Recently there have been concerns raised about prolonged exposure to placebo and ineffective therapy during the course of an add-on regulatory trial for new antiepileptic drug approval (typically ∼6 months in duration), due to the potential risks of continued uncontrolled epilepsy for that period. The first meeting of the Research Roundtable in Epilepsy on May 19–20, 2016, focused on "Reducing placebo exposure in epilepsy clinical trials, " with a goal of considering new designs for epilepsy regulatory trials that may be added to the overall development plan to make it, as a whole, safer for participants while still providing rigorous evidence of effect. This topic was motivated in part by data from a meta-analysis showing a 3- to 5-fold increased rate of sudden unexpected death in epilepsy in participants randomized to placebo or ineffective doses of new antiepileptic drugs. The meeting agenda included rationale and discussion of different trial designs, including active-control add-on trials, placebo add-on to background therapy with adjustment, time to event designs, adaptive designs, platform trials with pooled placebo control, a pharmacokinetic/pharmacodynamic approach to reducing placebo exposure, and shorter trials when drug tolerance has been ruled out. The merits and limitations of each design were discussed and are reviewed here.